Oscillations Control of Rocking-Block-Type Buildings by the Addition of a Tuned Pendulum - Luca Collini; Rinaldo Garziera; Kseniia Riabova; Mariya Munitsyna; Alessandro Tasora (Shock and Vibration)
This study deals with the dynamical evolutions exhibited by a simple mechanical model of building, comprising a parallelepiped standing on a horizontal plane. The main goal is the introduction of a pendulum in order to reduce oscillations. The theoretical part of the work consists of a Lagrange formulation and Galerkin approximation method, and dry friction has also been considered. From the analytical/numerical simulations, we derive some important conclusions, providing us with the tools suitable for the design of absorbers in practical cases.